Evaluación de la sustentabilidad ambiental en el cultivo florícola del sector Samilpamba, parroquia Tanicuchí, provincia de Cotopaxi. - Ortega Escobar, Luis Gerardo (2023)
Ecuador's flower cultivation stands out worldwide for its quality, generating profitable activities for a wide variety of companies and workers from different sectors; But, as it is a monoculture, the impact it causes on the environment must be taken care of, ensuring an environmentally sustainable process. The present study consisted of evaluating the sustainability of flower cultivation in the Samilpamba sector of the Tanicuchí parish, province of Cotopaxi; To carry out the research, a qualitative approach was used with exploratory, descriptive and explanatory methods, following a Sustainability Assessment methodology based on PER-type Indicators (SIA) (pressure, state and response) established in a survey and two checklists, the study population was 213 workers in the area; Finally, a proposal was made to improve certain weak aspects of the locality's cultivation process. The ratings of the indicators were: 100% good in pressure indicators, 70.22% grouped average of high and very high level in state indicators and 100% in compliance with the result indicators. A sustainable management proposal was developed to improve the minor problems of waste management, remedy the level of knowledge of workers and encourage the sector to increase its international certificates. It is concluded that Samilpamba's flower cultivation was in a favorable sustainability situation, thanks to this it has the main international sustainability certificate provided by the Rainforest Alliance organization, which demonstrates its commitment to the environment.